2019
DOI: 10.1021/acs.orglett.9b00083
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Activated Divergent Reactivity of Dienones: Dimerization in Neat Conditions and Regioselective E to Z Isomerization in the Solvent

Abstract: 2,4-Dienones undergo visible-light-promoted, photocatalyst-free dimerization in neat conditions to provide cyclohexene derivatives stereoselectively through cascade rearrangement pathways, whereas regioselective E → Z isomerization of the more dienophilic double bond takes place exclusively in nitromethane. On the basis of intermediate isolation and computational DFT studies, the dimerization reaction is proposed to proceed via s-trans to s-cis isomerization/regioselective E → Z isomerization/Diels−Alder cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…During our previous study under photochemical conditions also, we had not detected/isolated any dimerized product 3 arising from intermediate I . This may be ascribed to the fact that photoabsorption by the E ‐isomer excites the molecule to a higher energy state from where the formation of Z ‐isomer via the biradical mechanism may be a facile and viable process than oxa‐6π‐electrocyclization; subsequently the Z ‐isomer underwent rapid dimerization to afford 2 as the only isolated product . These results support the rationale behind the isolation of dimerized products 2 (previous work) and 3 (this work) exclusively under photochemical and thermal conditions, respectively.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…During our previous study under photochemical conditions also, we had not detected/isolated any dimerized product 3 arising from intermediate I . This may be ascribed to the fact that photoabsorption by the E ‐isomer excites the molecule to a higher energy state from where the formation of Z ‐isomer via the biradical mechanism may be a facile and viable process than oxa‐6π‐electrocyclization; subsequently the Z ‐isomer underwent rapid dimerization to afford 2 as the only isolated product . These results support the rationale behind the isolation of dimerized products 2 (previous work) and 3 (this work) exclusively under photochemical and thermal conditions, respectively.…”
Section: Resultssupporting
confidence: 83%
“…We have quite recently reported that intermediate I underwent dimerization under photochemical conditions to yield 2 through an uphill E / Z isomerization of C 2 −C 3 double bond followed by a Diels‐Alder cycloaddition . In the present study carried out under thermal conditions, we observed the formation of dimerized product 3 exclusively.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations